2016
DOI: 10.1021/acsami.6b04403
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Colorectal Cancer Stem-Like Cells with Anti-CD133 Antibody-Conjugated SN-38 Nanoparticles

Abstract: Cancer stem-like cells play a key role in tumor development, and these cells are relevant to the failure of conventional chemotherapy. To achieve favorable therapy for colorectal cancer, PEG-PCL-based nanoparticles, which possess good biological compatibility, were fabricated as nanocarriers for the topoisomerase inhibitor, SN-38. For cancer stem cell therapy, CD133 (prominin-1) is a theoretical cancer stem-like cell (CSLC) marker for colorectal cancer and is a proposed therapeutic target. Cells with CD133 ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 50 publications
0
63
0
Order By: Relevance
“…glycol)-poly(3-caprolactone) (mPEG-PCL) nanoparticles loaded with anticancer drug 7-ethyl-10-hydroxy-camptothecin (SN-38). 33 The in vitro and in vivo studies showed that CD133targeting nanoparticles have increased cytotoxicity and inhibited tumor growth in HCT116 cells and mouse xenogra models, respectively, compared with the none antibody-targeted nanoparticles. In this case, the therapeutic effects on CRC have been enhanced by the CD133 antibody conjugates because the chemotherapeutic agent SN-38 is efficiently guided to the overexpressed CD133 markers at the tumor site.…”
Section: Systemmentioning
confidence: 98%
“…glycol)-poly(3-caprolactone) (mPEG-PCL) nanoparticles loaded with anticancer drug 7-ethyl-10-hydroxy-camptothecin (SN-38). 33 The in vitro and in vivo studies showed that CD133targeting nanoparticles have increased cytotoxicity and inhibited tumor growth in HCT116 cells and mouse xenogra models, respectively, compared with the none antibody-targeted nanoparticles. In this case, the therapeutic effects on CRC have been enhanced by the CD133 antibody conjugates because the chemotherapeutic agent SN-38 is efficiently guided to the overexpressed CD133 markers at the tumor site.…”
Section: Systemmentioning
confidence: 98%
“…In this study, the influence of keratin substrate on the formation of HT29 spheroid‐like structures with stem cell properties was investigated. To this end, we evaluated and characterized the formation of sphere‐like structures and expression of CD133, as a specific surface marker of colorectal CSLCs,, and stemness‐related genes on keratin in comparison to collagen substrate. To the best of our knowledge, this is the first report on using keratin substrate for CSLCs’ enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…With the present NANO Pt‐Pan preparation, Panitumumab–EGFR binding facilitates targeted uptake into EGFR overexpressing CRC cells. Unlike other ligand‐modified nanomedicines with enhanced cell/tumor uptake, Panitumumab in NANO Pt‐Pan can suppress EGFR activation in CRC cells, thus improving antiproliferative effects and Pt drug efficacy. Moreover, NANO Pt‐Pan likely protects the Pt drug from degradation, resulting in increased circulation times and greater uptake into CRC cells.…”
Section: Introductionmentioning
confidence: 99%